2022
DOI: 10.1155/2022/9556880
|View full text |Cite|
|
Sign up to set email alerts
|

Predictive Value of Preoperative Dynamic Contrast-Enhanced MRI Imaging Features in Breast Cancer Patients with Postoperative Recurrence Time

Abstract: Although the implementation of surgery has reduced the mortality of breast cancer, postoperative recurrence is still an important problem bothering patients. DCE-GMRI can not only clearly display the morphological characteristics of breast lesions but also dynamically observe the blood perfusion of the lesions. On account of this, we explored the predictive value of preoperative dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) imaging features in breast cancer patients on postoperative recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Diffusion-weighted imaging (DWI) and dynamic contrast-enhanced (DCE) MRI has advantages in predicting the efficacy, prognosis, and biological characteristics of CRT. (6)(7)(8). In this study, patients with middle and low locally advanced READ who received neoadjuvant radiotherapy and chemotherapy were selected as the subjects.…”
Section: Investigating the Wnt/tcf Pathway And The Value Of Dce-mri I...mentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) and dynamic contrast-enhanced (DCE) MRI has advantages in predicting the efficacy, prognosis, and biological characteristics of CRT. (6)(7)(8). In this study, patients with middle and low locally advanced READ who received neoadjuvant radiotherapy and chemotherapy were selected as the subjects.…”
Section: Investigating the Wnt/tcf Pathway And The Value Of Dce-mri I...mentioning
confidence: 99%
“…Such a development is a key step toward identifying those radiomics features that can be associated with the physiology and microenvironment of the tumor and its surrounding tissues in human cancer studies. DCE-MRI has been established as a useful, noninvasive, and non-ionizing method for quantitative evaluation and characterization of tumor microvasculature and permeability parameters [60][61][62][63][64][65][66][67][68][69][70] . DCE-MRI experiment is performed by applying a fast T1-weighted MR pulse sequence to repeatedly image the volume of interest during the intravenous injection of a contrast agent (CA).…”
Section: -Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%